Subnational Governance and Conflict : The Merits of Subnational Governance as a Catalyst for Peace - Wolff, Stefan (World Bank, Washington, DC, 2020)
The potential for subnational governance to serve as a catalyst of peace has been widely recognized. It is reflected in the frequent inclusion of subnational governance arrangements in political settlements. The study seeks to analyze the merits and risks of subnational governance as a conflict mitigation mechanism within the framework of political settlement processes. This work is a contribution to the broader effort to close the knowledge gap on how development interventions can support the transition from war to peace. The findings are largely informed by in-depth analysis of seven case studies of countries where subnational governance arrangements have been applied and proposed as a tool for mitigating violent conflict. These include Kenya, the Philippines, Somalia, Myanmar, Bosnia and Herzegovina, Yemen, and Mali.